Optimizing geometrical structure of a residential parabolic solar collector relying on hydrothermal assessment and second law analysis - Malekshah, Emad Hasani; Tayebi, Tahar; Sajadi, S. Mohammad; Jalili, Bahram; Jalili, Payam; Aybar, Hikmet S. (Elsevier Sci Ltd, 2023)
Researchers are interested in the optimization of thermal systems due to the rising demand towards renewable and green energy to reduce greenhouse gasses and expenses. To achieve this, the present work aims to conduct the numerical modeling on the residential scale trough solar collector. For this purpose, the lattice Boltzmann method is employed with special treatment for the curved physical boundaries. To enhance the thermal capa-bility of the solar collector, the CuO-water nanofluid is utilized, which its thermal conductivity is estimated using Koo-Kleinstreuer and Li (KKL) model. Furthermore, the Brownian motion effect on the dynamic viscosity is taken into account. In addition, the local and volumetric second law analysis is performed. Besides, the heat line visualization is done to capture the path-line of heat energy within the solar collector. The thermal distribution, flow field, local entropy production (i.e. fluid friction irreversibility and heat transfer irreversibility maps), volumetric entropy generation, Bejan number, and average Nusselt number are the studied items in terms of the governing parameters. The Rayleigh number (103 <= Ra <= 106), CuO nanoparticle concentration (phi = 0, 0.01, 0.02, 0.03, 0.04) and four structural design of the solar collector (Single-pipe, Double-pipe, Triple-pipe, Quadruple-pipe) are assumed as the governing parameters.
Keywords: Trough solar collector; Hydrothermal analysis; Second law analysis; Lattice Boltzmann method; CuO-water nanofluid